2019
DOI: 10.22207/jpam.13.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Investigation of Vancomycin, Teicoplanin and Linezolid Resistance Among Enterococcus spp. Isolated from Children Diarrhea

Abstract: Vancomycin-resistant Enterococci(VRE) were common among Enterococcus. faecalis and Enterococcus faecium. Teicoplanin resistance or sensitivity can determine the VRE phenotypes whether VanA (Van R /tec R) or VanB (Van R / tec s). Linezolid resistance among VRE regards an newly emerged health problem. Infection with LRVRE or TRLRVRE pushan hazardous alert for hard to heal illness. Twenty eight Enterococcus spp. isolates were recovered from children diarrhea after their inoculation on m-EI chromogenic agar. Antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 45 publications
0
6
6
Order By: Relevance
“…However, the prevalence of VRE in our study was lower than the report from Ireland (44.1%) (4), Germany (26.1%) (32) Brazil (23.4%) (1), India (19.6%) (33), Saud Arabia (17.3%) (5) and Iraq (46.4%) (17). The lower prevalence in the present study might be due to the variation in study settings in which most of the previous countries have been using oral and intravenous vancomycin massively for human diseases (34,35), and variation in study participants in which in the previous studies most of the study participants were hospitalized patients and critically ill patients in ICU who were frequently exposed to different antibiotics and experienced insertion of external devices like catheter (7).…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…However, the prevalence of VRE in our study was lower than the report from Ireland (44.1%) (4), Germany (26.1%) (32) Brazil (23.4%) (1), India (19.6%) (33), Saud Arabia (17.3%) (5) and Iraq (46.4%) (17). The lower prevalence in the present study might be due to the variation in study settings in which most of the previous countries have been using oral and intravenous vancomycin massively for human diseases (34,35), and variation in study participants in which in the previous studies most of the study participants were hospitalized patients and critically ill patients in ICU who were frequently exposed to different antibiotics and experienced insertion of external devices like catheter (7).…”
Section: Discussioncontrasting
confidence: 83%
“…Moreover, the present study also showed that 49.6% of Enterococci isolates were multidrug resistant. This result is lower than the ndings in Iraq (85.7%) (17) and Ethiopia 80.8% (41). In contrary, the result is higher than the nding in Ethiopia 29.5% (16).…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Ireland (44.1%) [4], Germany (26.1%) [32] Brazil (23.4%) [1], India (19.6%) [33], Saud Arabia (17.3%) [5] and Iraq (46.4%) [17] where these studies were conducted on the population where HIV status not determined. The lower prevalence in the present study might be due to the variation in study settings in which most of the previous countries have been using oral and intravenous vancomycin massively for human diseases [34,35], and variation in study participants where the previous studies participants were hospitalized patients and critically ill patients in ICU who were frequently exposed to different antibiotics and experienced insertion of external devices like catheter [7].…”
Section: Plos Onementioning
confidence: 99%
“…Furthermore, few options are left for management of diseases caused by VRE, and hence causing increased mortality on infected individuals. VRE now represent approximately one third of Enterococcus isolates [6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%